Workforce agility in startup employees: The role of psychological empowerment, emotional intelligence and job autonomy - Hasna Uzzakiyah; Galang Lufityanto (HUMANITAS published by Universitas Ahmad Dahlan., 2025)
Workforce Agility (WFA) is crucial for startup companies, particularly in unexpected situations. Research shows that WFA significantly contributes to an organization's ability to thrive amidst uncertainty and competitive challenges. WFA can be influenced by both internal and external factors. In this study, psychological empowerment (PE) and emotional intelligence (EI) are represented the internal factors, while job autonomy (JA) served as the external factor. This research aims to explore the relationships between PE and EI on WFA with JA as grouping variable. A quantitative approach was utilized, involving 180 employees from various startups. Multiple regression analysis was conducted to assess the relationships between PE, EI, and WFA, categorized into three levels of JA. The results indicated that PE and EI simultaneously have a significant positive impact on WFA. The model explained 52% of the variance (R² = 0.52, F=93.8, p< 0.01). The study concluded that enhancing PE and EI among startup employees can improve their WFA. However, when JA levels segmented participants, only those in the low and medium JA groups exhibited a relationship between PE and EI on WFA. Thus, PE and EI can only increase WFA in subjects with low and medium level of JA.